Kemapanan Di Usia Pensiun Melalui Investasi Real Property - , Rasi Garindra Saksono, Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Objective to be achieved in this study was to identify ways to remain wealth at the age of retirement through real property investments, in this case is home or residence, especially in the areas of Jakarta. In the end, people will hopefully have a better view. Wealthiness is the condition to be achieved by each individual. However, when entering retirement, the level of wealthiness will decrease. The way to cope is by investing. There are many types of investments that can be selected. One of them is real property with a specialty in home or residence. By using the formula of Income Approach, will be able to decide the amount of revenue to be gained from renting a house or residence which has been held as a form of investment. Therefore, a person who has retired and no longer have a source of income can still maintain his life without having to depend on others. Revenues derived from the lease of real property can be used to meet the needs of everyday life when retirement.